물리적 처리에 의한 강력분 밀가루 Gliadin의 항원성 변화 - 강보경(Bo-Kyeong Kang); 김꽃봉우리(Koth-Bong-Woo-Ri Kim); 김민지(Min-Ji Kim); 박시우(Si-Woo Bark); 박원민(Won-Min Pak); 김보람(Bo-Ram Kim); 안나경(Na-Kyung Ahn); 최연욱(Yeon-Uk Choi); 최정수(Jung-Su Choi); 최호덕(Ho-Duk Choi); 안동현(Dong-Hyun Ahn) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
This study was conducted to evaluate the effects of physical treatments on the antigenicity of gliadin in strong wheat flour. Strong wheat flour was treated with an autoclave (5, 10, 30, 50 min), a microwave (1, 5, 10 min), or both (10, 30, 50 min/ 5, 10 min), followed by SDS-PAGE, immunoblotting, and Ci-ELISA using anti-gliadin IgG. The results indicated that the binding ability of IgG to gliadin in strong wheat flour slightly decreased after autoclaving or autoclaving/microwaving. In particular, the binding ability was reduced to about 87% after autoclaving for 50 min and to 89% after autoclaving/microwaving (50/5 min). In addition, gliadin bands in the 50 min autoclaved group disappeared in both SDS-PAGE and immunoblotting. On the other hand, the antigenicity of gliadin was unaffected by microwaving alone. In conclusion, the results of this study suggest that autoclaving may reduce the antigenicity of gliadin in strong wheat flour. 본 연구에서는 가압가열 및 microwave 처리가 gliadin의 항원성에 미치는 영향을 살펴보기 위해 강력분에 가압가열과 microwave를 단독 또는 병행으로 처리하여 Ci-ELISA, SDS-PAGE 및 immunoblotting을 실시하였다. 가압가열 처리의 경우 시간이 길어질수록 IgG와의 결합력이 감소하였으며, 특히 50분 처리구에서 약 87%로 가장 낮은 결합력을 보였다. 또한 SDS-PAGE와 immunoblotting 결과에서도 무처리구에서 강하게 보였던 gliadin band가 가압가열 처리에 의해 거의 소실되고 항체와 반응하지 않았다. 가압가열 및 microwave를 병행 처리 시도 마찬가지로 gliadin의 결합력이 감소하였으며, 처리구 중 가압가열 50분, microwave 5분 처리구에서 약 93%로 가장 낮은 결합력을 보였다. 반면 microwave를 단독으로 처리한 경우에는 일부 단백질의 변화는 관찰되었으나, 항원성 감소에는 효과가 없음을 확인하여 단백질 변화가 항원성에는 큰 효과를 준 것 같지 않다. 이상의 결과를 통해 가압가열 단독 처리 및 가압가열 및 microwave의 병행처리 시 gliadin의 항원성이 감소함을 확인하였다.